A graphene composite hydrogel, aerogel and preparation method and application thereof
By providing radical reactions to prepare graphene composite hydrogel or gas gel, the problem of precious metal nanoparticles in graphene composite materials is solved, and the efficiency of the uniform dispersing of materials, catalytic performance improvement, and material recovery are achieved.
Patent Information
- Application Number
- CN202310274825.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-20
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-03-20
AI Technical Summary
Precious metal nanoparticles in existing graphene composite materials are prone to agglomeration, resulting in limited catalytic and electrical properties and difficult to recover.
By dispatching the mixture of graphene dispersing liquid, precious metal compounds, alcohol water -soluble reducing agents, and magnetic nanoparticles for radiation response, prepare graphene composite hydrogel or gas gel, and the precious metal nanoparticles are evenly distributed in graphene In terms of frame structure, avoid reunion, and realize material recycling through magnetic nanoparticles.
The uniform dispersion of precious metal nanoparticles in graphene composite materials is achieved, which improves catalytic performance and reusability, and achieves efficient recycling of materials through magnetic force.
Smart Images

Figure CN116272867B_ABST
Abstract
Description
Technical Field
[0001] This patent relates to a graphene composite hydrogel, aerogel and their preparation method and application. Background Art
[0002] Carbon material is the most common and wonderful material on earth. It can form the world's hardest diamond and the softest graphite. In the past 20 years, carbon nanomaterials have been at the forefront of scientific and technological innovation. Graphene is composed of a dense layer of carbon atoms wrapped in a honeycomb crystal lattice. It is the thinnest two-dimensional material in the world, with a thickness of only 0.35nm. This special structure contains rich and novel physical phenomena, which makes graphene exhibit many excellent properties. For example, the strength of graphene is the highest among the tested materials, reaching 130GPa, which is more than 100 times that of steel; its carrier mobility reaches 15000cm 2 ·V -1 ·s -1 , which is twice the highest mobility of indium antimonide materials known so far, and more than 10 times the mobility of commercial silicon wafers. Under certain conditions (such as low-temperature quenching, etc.), its mobility can even reach 250,000 cm 2 ·V -1 ·s -1 ; Its thermal conductivity can reach 5000W·m -1 ·K -1 , which is three times that of diamond; it also has special properties such as room temperature quantum Hall effect and room temperature ferromagnetism. Due to its excellent mechanical and optoelectronic properties, combined with its special single atomic layer planar two-dimensional structure and its high specific surface area, various flexible electronic devices and functional composite materials based on graphene can be prepared.
[0003] From the perspective of practical application, the transformation of nanographene materials into macrographene materials is undoubtedly a very valuable research direction. Precious metals generally include Au, Ag and platinum group metals Ru, Rh, Pd, Os, Ir and Pt, which are expensive metals. Precious metal nanoparticles have excellent optical, electrical, magnetic and catalytic properties that are different from the bulk materials. They have a large specific surface area, strong electrical conductivity and reactivity, and many surface active sites. They are a class of excellent electroanalytical and electrocatalytic nanomaterials and are widely used in many fields such as chemistry and biology. The preparation of macrographene-precious metal inorganic nanoparticle composites by combining multifunctional precious metal inorganic nanoparticles with macrographene materials will undoubtedly bring great value to the industry. At present, there have been a lot of studies on macrographene materials or graphene-precious metal binary macrocomposites, but there are few reports on the preparation and research of macroscopic three-dimensional graphene-based bulk gel materials (especially macrographene-iron tetroxide-precious metal ternary composite aerogel materials).
[0004] For example, Chinese patent document CN104250005A discloses a graphene aerogel and its preparation method and application. The application scope of the simple graphene aerogel prepared in the patent is limited. It does not combine the multifunctional noble metal nanoparticles with the macroscopic graphene aerogel, and is subject to certain restrictions in practical applications. For another example, Gao Chao et al. reported (Graphene nanosheets decorated with Pd, Pt, Au, and Ag nanoparticles: Synthesis, characterization, and catalysis application. Science China Chemistry, 2011.54(2):397-404.) a powder material of noble metal (such as Ag, Au, Pt and Pd) and graphene. The material uses graphene as a carrier and is composited with noble metal nanoparticles for catalytic reaction. However, it still belongs to nano powder material. The common disadvantage of nano powder material is that it is easy to agglomerate. In practical applications, it has the defects of low application efficiency and difficult recovery.
[0005] If graphene and precious metal nanoparticles are directly blended to prepare a composite material, the preparation method will cause serious agglomeration of precious metal nanoparticles, resulting in the utilization efficiency of the excellent properties of precious metal inorganic nanoparticles such as good catalytic and electrical properties being limited due to the agglomeration of nanoparticles, and it is impossible to provide options for the rapidly developing application industry. Chinese patent document CN106268631A discloses a graphene-precious metal nanoparticle composite water, aerogel and its preparation method and application. In the graphene-precious metal nanoparticle composite aerogel prepared by the patent, the precious metal nanoparticles are evenly distributed on the graphene aerogel frame, which effectively solves the problem of serious agglomeration of precious metal nanoparticles, but this aerogel has the defect of being difficult to recycle during actual application.
[0006] Therefore, how to ensure that precious metal nanoparticles can be evenly dispersed in graphene composites while solving the defect that graphene composites are difficult to recycle is a problem that needs to be solved urgently. Summary of the invention
[0007] The technical problem to be solved by the present application is to overcome the defect that graphene composite materials in the prior art are difficult to recycle, and provide a graphene composite hydrogel, aerogel and their preparation method and application. The preparation method of the graphene composite hydrogel and aerogel in the present application is simple to operate and environmentally friendly. The prepared graphene composite hydrogel and aerogel have a large specific surface area, and the precious metal nanoparticles can be evenly loaded on the framework structure of the graphene composite hydrogel and aerogel without agglomeration, and also have the advantage of easy recycling, and when applied in the field of catalytic degradation, they have excellent catalytic performance and good reusability.
[0008] The present invention solves the above technical problems through the following technical solutions.
[0009] The present invention provides a method for preparing a graphene composite hydrogel, which comprises the following steps:
[0010] The graphene composite hydrogel can be obtained by subjecting a mixed solution of graphene oxide dispersion, noble metal compound, alcohol water-soluble reducing agent and magnetic nanoparticles to irradiation reaction;
[0011] Wherein, in the mixed solution, the mass fraction of the alcohol water-soluble reducing agent is 2%-90%; and the concentration of the magnetic nanoparticles is 0.0010-0.0250 mmol / ml.
[0012] In the present invention, the preparation method of the graphene oxide dispersion can be conventional in the art, preferably prepared by an oxidative exfoliation graphite method (i.e., a Hummers method), and more preferably prepared by the following steps: ① pre-oxidation: pour 9-11 g of graphite, 130-160 mL of concentrated sulfuric acid, and 40-60 mL of concentrated nitric acid into water, stir at room temperature for 22-26 h, add 0.8-1.2 L of deionized water, filter, and dry; repeat the above pre-oxidation process 2-3 times to obtain pre-oxidized graphite; ② thermal expansion: thermally expand the pre-oxidized graphite of step ① at 400-900 ° C for 10-30 s to obtain thermally expanded oxidized graphite; ③ thermally expand 4-6 g of graphite obtained from step ② with 280-320 mL of concentrated sulfuric acid, 4.1-4.3 g A mixture of K2S2O8 and 6.1-6.3g of phosphorus pentoxide is heated at 80-90°C, water is added for filtration and washing, and then dried to obtain pre-oxidized thermal expansion graphite; ④ 4-6g of the pre-oxidized thermal expansion graphite of step ③ is mixed with 180-220mL of concentrated sulfuric acid at 0-5°C, 14-16g of potassium permanganate is added, and the mixture is reacted at 34-36°C for 1.5-2.5h, and then 18-22mL of hydrogen peroxide is added, the mixture is allowed to stand, centrifuged for washing, and water is added for stirring.
[0013] In the present invention, the precious metal compound may be conventional in the art, preferably a water-soluble precious metal compound. The water-soluble precious metal compound is preferably a water-soluble precious metal acid and / or a water-soluble precious metal salt. The water-soluble precious metal acid may be conventional in the art, preferably one or more of chloroauric acid, chloroplatinic acid, chloropalladic acid and chlororhodic acid. The water-soluble precious metal salt may be conventional in the art, preferably one or more of silver nitrate, potassium chlororuthenate, potassium chlororhodate, ruthenium trichloride, rhodium trichloride and iridium trichloride. The water-soluble precious metal compound is preferably chloroauric acid, chloroauric acid and chloroplatinic acid, or, silver nitrate, potassium chlororuthenate and chloroplatinic acid. Those skilled in the art will appreciate that water solubility means being able to dissolve in water at 5-45°C.
[0014] In the present invention, the mass ratio of the graphene oxide to the noble metal compound is preferably (1:0.01)-(1:0.4), for example 1:0.1 or 1:0.2. If the amount of the noble metal compound added is too high, the size of the noble metal nanoparticles loaded in the obtained graphene composite hydrogel is large, and the nanoparticles are prone to agglomeration.
[0015] In the present invention, the alcohol water-soluble reducing agent can be one or more of methanol, ethanol, propanol, isopropanol, butanol, butanediol, isobutanol, ethylene glycol, propylene glycol, glycerol, octanediol and polyvinyl alcohol, such as ethanol, isopropanol, methanol and ethylene glycol, methanol, propanol and butanediol, methanol, glycerol and octanediol, or methanol, propylene glycol, glycerol and octanediol.
[0016] Wherein, when the alcohol water-soluble reducing agent is methanol and ethylene glycol, the volume ratio of the methanol to the ethylene glycol is preferably (1-3):(1:3), for example, 1:1.
[0017] Among them, when the alcohol water-soluble reducing agent is methanol, propanol and butanediol, the volume ratio of the methanol, the propanol and the butanediol is preferably (1-3):(1:3):(1:3), for example, 1:1:1.
[0018] Among them, when the alcohol water-soluble reducing agent is methanol, glycerol and octanediol, the volume ratio of the methanol, the glycerol and the octanediol is preferably (1-3):(1:3):(1:3), for example, 1:1:1.
[0019] Among them, when the alcohol water-soluble reducing agent is methanol, propylene glycol, glycerol and octanediol, the volume ratio of the methanol, the propylene glycol, the glycerol and the octanediol is preferably (1-3):(1:3):(1:3):(1:3), for example 1:1:1:1.
[0020] In the present invention, the mass percentage of the alcohol water-soluble reducing agent in the mixed solution is preferably 5%-80%, more preferably 10%-70%, for example 15%, 20% or 50%. When the content of the alcohol water-soluble reducing agent is small, the obtained graphene composite hydrogel is graphene-noble metal inorganic nanocomposite particles suspended in the tube, and a continuous wet graphene composite hydrogel with a certain self-supporting mechanical strength cannot be obtained. When the content of the alcohol water-soluble reducing agent is large, not only the cost is increased, but also the dispersion of graphene oxide and noble metal compounds in the solution is poor, and it is not easy to obtain a continuous graphene composite hydrogel.
[0021] In the present invention, the type of the magnetic nanoparticles can be one or more of ferroferric oxide (Fe3O4) nanoparticles, nano-iron particles, nano-nickel particles, nano-cobalt particles or nano-manganese particles, such as ferroferric oxide (Fe3O4) nanoparticles, nano-iron particles, nano-nickel particles, nano-cobalt particles and nano-manganese particles, nano-iron particles and nano-nickel particles, or nano-ferroferric oxide particles and nano-nickel particles. It can be understood by those skilled in the art that the magnetic nanoparticles refer to substances that can generate magnetism under the action of a magnetic field, generally hard magnetic substances.
[0022] In the present invention, the particle size of the magnetic nanoparticles may be 50-500 nm, such as 10-100 nm, 100-200 nm or 200-500 nm.
[0023] In the present invention, in the mixed solution, the concentration of the magnetic nanoparticles is preferably 0.0050-0.0200 mmol / ml, for example 0.008 mmol / ml. When the concentration of the magnetic nanoparticles is low, the resulting graphene composite hydrogel cannot be attracted by a magnet. When the concentration of the magnetic nanoparticles is high, the structure of the resulting graphene composite hydrogel is unstable.
[0024] In the present invention, in the mixed solution, the concentration of the graphene oxide is preferably 1-20 mg / mL, more preferably 2-10 mg / mL, for example 2 mg / mL.
[0025] In the present invention, the radiation reaction device may be a radiation reactor. The radiation reactor may be cylindrical in shape.
[0026] In the present invention, the atmosphere of the irradiation reaction can be an oxygen-free atmosphere or an air atmosphere, preferably an oxygen-free atmosphere. The oxygen-free atmosphere is preferably nitrogen and / or argon.
[0027] In the present invention, the irradiation reaction can be carried out by irradiation with high-energy rays. The high-energy rays are preferably gamma rays or electron beam rays. The gamma rays are preferably cobalt 60 gamma rays.
[0028] The dosage of the high energy rays is preferably 50-800 kGy, more preferably 110-600 kGy, for example 200 kGy.
[0029] The dose rate of the high energy rays is preferably 0.1-15 kGy / hour, more preferably 1-15 kGy / hour, for example 10 kGy / hour.
[0030] In a preferred embodiment, the method for preparing the graphene composite hydrogel comprises the following steps:
[0031] The graphene composite hydrogel can be obtained by subjecting a mixed solution of graphene oxide dispersion, noble metal compound, alcohol water-soluble reducing agent and magnetic nanoparticles to irradiation reaction;
[0032] In the mixed solution, the concentration of the graphene oxide dispersion is 1-20 mg / mL, the mass ratio of the graphene oxide to the precious metal compound is (1:0.01)-(1:0.4), the alcohol water-soluble reducing agent is ethanol, and the mass fraction of the alcohol water-soluble reducing agent is 2%-90%; the concentration of the magnetic nanoparticles is 0.0010-0.0250 mmol / ml.
[0033] In another preferred embodiment, the method for preparing the graphene composite hydrogel comprises the following steps:
[0034] The graphene composite hydrogel can be obtained by subjecting a mixed solution of graphene oxide dispersion, noble metal compound, alcohol water-soluble reducing agent and magnetic nanoparticles to irradiation reaction;
[0035] Wherein, in the mixed liquid, the concentration of the graphene oxide dispersion is 1-20 mg / mL, the mass ratio of the graphene oxide to the precious metal compound is (1:0.01)-(1:0.4), the alcohol water-soluble reducing agent is ethanol, and the mass fraction of the alcohol water-soluble reducing agent is 2%-90%; the concentration of the magnetic nanoparticles is 0.0010-0.0250 mmol / ml, the atmosphere of the irradiation reaction is an oxygen-free atmosphere, the irradiation reaction is carried out by high-energy ray irradiation, the dose of the high-energy ray is 50-800 kGy, and the dose rate of the high-energy ray is preferably 0.1-15 kGy / hour.
[0036] The present invention also provides a graphene composite hydrogel prepared by the above preparation method.
[0037] In the present invention, the pore size distribution of the graphene composite hydrogel may be 10-100 μm.
[0038] In the present invention, the type of the noble metal nanoparticles in the graphene composite hydrogel may be one or more of gold, platinum, palladium, rhodium, silver, ruthenium and iridium.
[0039] In the present invention, the diameter of the noble metal nanoparticles in the graphene composite hydrogel may be 40-80 nm.
[0040] The present invention also provides a graphene composite hydrogel, which comprises graphene, noble metal nanoparticles and magnetic nanoparticles;
[0041] The noble metal nanoparticles can be evenly dispersed on the graphene; the pore size distribution of the graphene composite hydrogel is 10-100 μm.
[0042] The present invention also provides a method for preparing a graphene composite aerogel, which comprises the following steps: drying the graphene composite hydrogel as described above.
[0043] In the present invention, the drying may be freeze drying or supercritical carbon dioxide drying.
[0044] Wherein, the freeze-drying temperature may be -40°C.
[0045] The present invention also provides a graphene composite aerogel prepared by the above-mentioned preparation method.
[0046] In the present invention, the pore size distribution of the graphene composite aerogel may be 10-100 μm.
[0047] In the present invention, the type of the noble metal nanoparticles in the graphene composite aerogel may be one or more of gold, platinum, palladium, rhodium, silver, ruthenium and iridium.
[0048] In the present invention, the diameter of the noble metal nanoparticles in the graphene composite aerogel may be 40-80 nm.
[0049] The present invention also provides a graphene composite aerogel, which comprises graphene, noble metal nanoparticles and magnetic nanoparticles;
[0050] The noble metal nanoparticles can be evenly dispersed on the graphene; the pore size distribution of the graphene composite aerogel is 10-100 μm.
[0051] The present invention also provides a use of the graphene composite hydrogel or aerogel as described above in adsorbing organic solvents.
[0052] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0053] The reagents and raw materials used in the present invention are commercially available.
[0054] The positive and progressive effects of the present invention are:
[0055] 1. The raw materials of the present invention are graphene oxide dispersion, alcohol reducing agent, noble metal compound and magnetic nanoparticles. The raw materials are widely available and have high utilization rate. The graphene oxide raw materials used are completely gel-formed after reaction, the aqueous solution around the gel is transparent, and there is almost no loss of raw materials. The reducing agent is selected as the irradiation reaction system, the preparation process is simple, and harsh chemical reaction conditions are not involved, thus avoiding complex and difficult chemical reactions and purification processes. In the present invention, the graphene sheet provides loading sites for noble metal nanoparticles and ferrosoferric oxide, providing a carrier for the in-situ formation, uniform dispersion and applicability of the noble metal nanoparticles. The irradiation reduction reaction of the present invention is carried out at ambient temperature, the operation is simple, and it is expected to realize the industrialization of technology.
[0056] 2. The graphene composite hydrogel or aerogel obtained by the present invention is relatively pure, and is not doped with other elements except carbon, oxygen and precious metal elements;
[0057] 3. In the graphene hydrogel or aerogel prepared in the present invention, the noble metal nanoparticles are in-situ reduced on the graphene surface and uniformly loaded on the framework structure of the graphene composite hydrogel or aerogel, including the outer surface and the internal porous structure. The noble metal nanoparticles have good dispersibility and are slowly formed by adhering to the graphene sheet. The two are tightly combined without agglomeration, so that the prepared graphene composite hydrogel or aerogel is conducive to giving full play to the beneficial properties of the noble metal nanoparticles such as good catalytic and electrical properties in the process of absorbing organic solvents, and has great potential application value.
[0058] 4. The shape and size of the graphene composite hydrogel or aerogel of the present invention can be adjusted by using irradiation reactors of different shapes and sizes; its density can be controlled by changing the concentration of the reactants; it has a porous, macroporous structure with a pore size distribution between 10-100 μm and a relatively uniform structure; the precious metal nanoparticles are very evenly distributed with basically no agglomeration; it has a large specific surface area, good electrical conductivity, and excellent thermal conductivity.
[0059] 5. The graphene composite hydrogel or aerogel of the present invention can be contactlessly controlled by magnetic force, and the material can be easily recycled using magnets.
[0060] 6. The preparation method of the present invention can obtain single noble metal nanoparticle graphene composite hydrogel or aerogel of different noble metal types, and can also obtain graphene composite hydrogel or aerogel composited with two or more noble metal nanoparticles. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 This is a scanning electron microscope image of the graphene composite aerogel prepared in Example 1.
[0062] Figure 2This is a transmission electron microscope image of the graphene composite aerogel prepared in Example 1.
[0063] Figure 3 This is a picture of the graphene composite aerogel prepared in Example 1 being attracted by a magnet.
[0064] Figure 4 This is the appearance of the graphene composite hydrogel prepared in Comparative Example 2.
[0065] Figure 5 This is the appearance of the graphene composite hydrogel prepared in Example 1. DETAILED DESCRIPTION
[0066] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0067] In the following examples, the graphite used is provided by Sigma-Aldrich, and the graphite used is flake graphite with an average particle size of 50-500 μm. The remaining raw materials are provided by Sinopharm Chemical Reagent Co., Ltd. Among them, the particle size of the ferroferric oxide nanoparticles is 50-500 nm.
[0068] Example 1
[0069] (1) Preparation method of graphene oxide dispersion:
[0070] 10g of graphite, 150ml of 98% concentrated sulfuric acid, and 50ml of 65% concentrated nitric acid are added to a 500ml conical flask and stirred at room temperature for 24h. Slowly pour into 1L of water to filter and collect the solid, wash 3 times, and dry at 80℃ for 4 hours. Repeat the pre-oxidation process twice. The dried pre-oxidized graphite is placed in a box furnace and thermally expanded at 900℃ for 10s to obtain thermal expansion graphite oxide. In a 500ml wide-mouth conical flask, 5g of thermal expansion graphite oxide is mixed with 300ml of 98% concentrated sulfuric acid, 4.2g of K2S2O8, and 6.2g of phosphorus pentoxide, and heated at 80℃ for 4 hours, diluted with 2L of water, filtered and washed, and dried in air for 3 days to obtain pre-oxidized thermal expansion graphite. Mix 5 g of dry pre-oxidized thermal expansion graphite with 200 ml of 98% concentrated sulfuric acid at a low temperature of 0-5°C, add 15 g of potassium permanganate, slowly add, stir at 35°C for 2 hours, dilute with 2 L of water, let stand for 1 hour, then add 20 ml of 30% hydrogen peroxide, let stand for 2 days, centrifuge and wash, add water and stir, and a well-dispersed graphene oxide dispersion is obtained.
[0071] (2) mixing the graphene oxide dispersion obtained in step (1), chloroauric acid, ferroferric oxide nanoparticles and an alcoholic water-soluble reducing agent (ethanol) to obtain a mixed solution; wherein the concentration of graphene oxide is 2 mg / ml, the mass ratio of graphene oxide to chloroauric acid is 1:0.1, the magnetic nanoparticles are ferroferric oxide nanoparticles with a particle size of 10-100 nm, the concentration of the magnetic nanoparticles in the mixed solution is 0.008 mmol / ml, and the mass percentage of the alcoholic water-soluble reducing agent (ethanol) in the mixed solution is 40%.
[0072] (3) injecting the mixed solution obtained in step (2) into a cylindrical irradiation reactor and passing nitrogen to remove oxygen; irradiating the sealed irradiation reactor with a cobalt 60 gamma ray source to obtain a graphene composite hydrogel; wherein the dose of the cobalt 60 gamma ray is 200 kGy, and the dose rate of the cobalt 60 gamma ray is 10 kGy / hour.
[0073] (4) freeze-drying the graphene composite hydrogel obtained in step (3) at -40°C to obtain a dry cylindrical graphene composite aerogel.
[0074] Example 2
[0075] The difference from Example 1 is that the mass ratio of graphene oxide to chloroauric acid is 1:0.2, the particle size of ferroferric oxide nanoparticles is 100-200 nm, the alcohol water-soluble reducing agent is methanol and ethylene glycol, the volume ratio is 1:1, and the alcohol water-soluble reducing agent accounts for 10% of the mass percentage of the mixed solution.
[0076] Example 3
[0077] The difference from Example 1 is that the mass ratio of graphene oxide to chloroauric acid is 1:0.4, the particle size of ferroferric oxide nanoparticles is 200-500nm, the alcohol water-soluble reducing agent is isopropanol, and the alcohol water-soluble reducing agent accounts for 90% of the mass percentage of the mixed solution.
[0078] Example 4
[0079] The difference from Example 1 is that the magnetic nanoparticles are nano-iron particles, nano-nickel particles, nano-cobalt particles and nano-manganese particles, with a mass ratio of 1:1:1:1. The alcohol water-soluble reducing agent is methanol, propanol and butanediol, with a volume ratio of 1:1:1. The alcohol water-soluble reducing agent accounts for 50% of the mass percentage of the mixed solution.
[0080] Example 5
[0081] The difference from Example 1 is that the magnetic nanoparticles are nano-iron particles and nano-nickel particles, with a mass ratio of 1:1. The alcohol water-soluble reducing agent is methanol, glycerol, and octanediol, with a volume ratio of 1:1:1. The alcohol water-soluble reducing agent accounts for 2% of the mass percentage of the mixed solution.
[0082] Example 6
[0083] The difference from Example 1 is that the magnetic nanoparticles are nano-ferroferric oxide particles and nano-nickel particles, with a mass ratio of 1:1. The alcohol water-soluble reducing agent is methanol, propylene glycol, glycerol, and octanediol, with a volume ratio of 1:1:1:1. The mass percentage of the alcohol water-soluble reducing agent in the mixed solution is 5%.
[0084] Example 7
[0085] The difference from Example 1 is that the water-soluble noble metal acid and / or water-soluble noble metal salt is chloroauric acid and chloroplatinic acid, with a mass ratio of 1:1. The alcohol water-soluble reducing agent is methanol, propanol and butanediol, with a volume ratio of 1:1:1. The mass percentage of the alcohol water-soluble reducing agent in the mixed solution is 20%.
[0086] Example 8
[0087] The difference from Example 1 is that the water-soluble noble metal acid and / or water-soluble noble metal salt is silver nitrate, potassium chlororuthenate and chloroplatinic acid, with a mass ratio of 1:1:1. The alcohol water-soluble reducing agent is methanol, propanol and butanediol, with a volume ratio of 1:1:1. The mass percentage of the alcohol water-soluble reducing agent in the mixed solution is 15%.
[0088] Comparative Example 1
[0089] The difference from Example 1 is that the magnetic ferroferric oxide nanoparticles are replaced by soft magnetic manganese oxide nanoparticles of the same size. Graphene composite aerogel can be prepared, but it cannot be attracted by a magnet.
[0090] Comparative Example 2
[0091] The difference from Example 1 is that: ① the mass percentage of the alcohol water-soluble reducing agent in the graphene oxide mixed solution is 1%. ② the concentration of the magnetic nanoparticles is 0.001 mmol / ml. It is impossible to prepare a graphene composite aerogel with a stable structure.
[0092] Comparative Example 3
[0093] The difference from Example 1 is that: ① the mass percentage of the alcohol water-soluble reducing agent in the graphene oxide mixed solution is 95%. ② the concentration of the magnetic nanoparticles is 0.025 mmol / ml. It is impossible to prepare a graphene composite aerogel with a stable structure.
[0094] Comparative Example 4
[0095] The difference from Example 1 is that: ① the mass ratio of graphene oxide to chloroauric acid is 1:0.6.
[0096] ② The mass percentage of the alcohol water-soluble reducing agent in the graphene oxide mixed solution is 1%.
[0097] ③The concentration of magnetic nanoparticles is 0mmol / ml. It is impossible to prepare a graphene composite aerogel with a stable structure. It cannot be attracted by a magnet.
[0098] Comparative Example 5
[0099] The difference from Example 1 is that: ① the mass ratio of graphene oxide to chloroauric acid is 1:0.6.
[0100] ② The mass percentage of the alcohol water-soluble reducing agent in the graphene oxide mixed solution is 95%.
[0101] ③ The concentration of magnetic nanoparticles is 0.05mmol / ml. It is impossible to prepare graphene composite aerogel with a stable structure.
[0102] Comparative Example 6
[0103] The difference from Example 1 is that ethanol is replaced by ethylenediamine, which has a poor effect and cannot prepare a graphene composite aerogel with a stable structure.
[0104] Comparative Example 7
[0105] The difference from Example 1 is that the mass ratio of graphene oxide to chloroauric acid is 1:0.6.
[0106] Comparative Example 8
[0107] The difference from Example 1 is that the mass percentage of the alcohol water-soluble reducing agent in the graphene oxide mixed solution is 1%, and a graphene composite aerogel with a stable structure cannot be prepared.
[0108] Comparative Example 9
[0109] The difference from Example 1 is that the mass percentage of the alcohol water-soluble reducing agent in the graphene oxide mixed solution is 95%, and a graphene composite aerogel with a stable structure cannot be prepared.
[0110] Comparative Example 10
[0111] The difference from Example 1 is that the concentration of magnetic nanoparticles is 0 mmol / ml, and the material presents an aerogel morphology but cannot be attracted by a magnet.
[0112] Comparative Example 11
[0113] The difference from Example 1 is that the concentration of magnetic nanoparticles is 0.05 mmol / ml, and a graphene composite aerogel with a stable structure cannot be prepared.
[0114] Effect Example 1
[0115] The graphene composite aerogel prepared in Example 1 was observed by scanning electron microscopy (500 times) and projection electron microscopy (at a scale of 200 nm), and the observation results were as follows: Figure 1 and Figure 2 shown.
[0116] Depend on Figure 1 It can be seen that the graphene composite aerogel prepared in Example 1 is porous and macroporous, with a relatively uniform structure and a pore size distribution between 10 and 100 μm. The scanning electron microscope images of the graphene composite aerogels prepared in Examples 2 to 8 are similar to those in Example 1.
[0117] Depend on Figure 2 It can be seen that the gold nanoparticles on the surface of the graphene composite aerogel prepared in Example 1 are uniformly distributed in size, with a diameter of 40-80 nm. The transmission electron microscopy images of the graphene composite aerogels prepared in Examples 2 to 8 are similar to those in Example 1.
[0118] The graphene composite aerogel prepared in Example 1 was subjected to a magnet attraction test, and the effect diagram is as follows: Figure 3 .Depend on Figure 3 It can be seen that graphene composite aerogel can be effectively attracted by magnets.
[0119] The appearance of the graphene composite hydrogels prepared in Example 1 and Comparative Example 2 were observed respectively, and the results were as follows: Figure 4 (Comparative Example 2) and Figure 5 (Example 1) shown. Figure 4 The graphene composite hydrogel structure is unstable and cannot be formed. It is in the form of nanopowder and finally settles to the bottom. Figure 5 The graphene composite hydrogel has a stable structure and a certain self-supporting mechanical strength.
[0120] Effect Example 2
[0121] The graphene composite aerogel prepared in Example 1 was tested for carbon-oxygen ratio, aerogel density and oil absorption performance. The test results are shown in Table 1.
[0122] Among them, X-ray photoelectron spectroscopy XPS is used to test the carbon content and oxygen content, and the carbon-oxygen ratio = carbon content / oxygen content.
[0123] Where density = mass / volume.
[0124] The oil absorption performance test takes the adsorption of n-decane as an example, and the oil absorption performance = oil absorption mass / mass of the graphene composite material.
[0125] Table 1
[0126] sample Carbon-oxygen ratio <![CDATA[Density (mg / cm 3 )]]> <![CDATA[Oil absorption performance Q w (g / g)]]> Example 1 8.00 3.0 60
[0127] As shown in 1, the graphene composite aerogel prepared in Example 1 has good oil absorption performance. The carbon-oxygen ratio, aerogel density and oil absorption performance of the graphene composite aerogels prepared in Examples 2 to 8 are similar to those in Example 1.
[0128] Effect Example 3
[0129] The degradation performance of the graphene composite aerogels prepared in Examples 1-6 and Comparative Examples 1-11 on nitrophenol (4NP) was tested respectively, and the test results are shown in Table 2.
[0130] The test conditions are as follows: The catalytic 4NP degradation process of graphene composite aerogel was measured by UV-VIS spectrometer with a scanning wavelength range of 200-700nm. During continuous stirring, 10mg of graphene composite aerogel was added as a catalyst to a 4NP (20ml 0.5mmol / L) solution, and then a freshly prepared NaBH4 aqueous solution (10ml 0.5mol / L) was quickly added to the above solution. All catalytic reactions were stirred at a speed of 150r / min in a 50ml beaker, and the reaction process was then detected by UV-VIS spectroscopy. The kinetic rate constant k of the first-order reaction can be expressed by the formula Calculate, where C0 is the initial concentration of 4-NP, C t is the concentration of 4NP in the reaction.
[0131] Table 2
[0132]
[0133]
[0134] As shown in Table 2, the graphene composite aerogels prepared in Examples 1-8 have good catalytic ability for 4NP, and have great potential application value in the fields of organic reaction catalytic synthesis such as small molecule electroanalysis and electrocatalysis, and the synthesis of petroleum organic intermediates.
[0135] Effect Example 4
[0136] The oil absorption performance test method in Example 1 was used to test the oil absorption performance of the graphene composite aerogel prepared in Example 1, and the test was repeated 7 times to test the reusability of the oil absorption performance. The test results are shown in Table 3.
[0137] Table 3
[0138] Number of cycles <![CDATA[Oil absorption performance Q wt (g / g)]]> 1 57.38 2 52.53 3 51.26 4 49.92 5 49.62 6 51.49 7 50.61
[0139] The oil absorption performance test method in Example 1 was used to test the oil absorption performance of the graphene composite aerogel prepared in Example 3, and the test was repeated 7 times to test the reusability of the oil absorption performance. The test results are shown in Table 4.
[0140] Table 4
[0141] Number of cycles <![CDATA[Oil absorption performance Q wt (g / g)]]> 1 58.46 2 56.38 3 56.89 4 55.37 5 57.26 6 54.48 7 53.35
[0142] Effect Example 5
[0143] The 4NP degradation performance of the graphene composite aerogel prepared in Example 1 was tested by the 4NP degradation performance test method of Effect Example 3, and the test was repeated 7 times to test the reusability of the 4NP degradation performance of the graphene composite aerogel. The test results are shown in Table 5.
[0144] Table 5
[0145] Number of cycles <![CDATA[Reaction kinetic rate constant (min -1 )]]> 1 0.12 2 0.12 3 0.11 4 0.12 5 0.11 6 0.12 7 0.11
[0146] It can be seen from Table 5 that the reaction kinetic rate constant of the graphene composite aerogel prepared in Example 1 remains substantially unchanged after being recycled 7 times, and the graphene composite aerogel has ideal reusability.
[0147] The 4NP degradation performance of the graphene composite aerogel prepared in Example 3 was tested by the 4NP degradation performance test method of Effect Example 3, and the test was repeated 7 times to test the reusability of the 4NP degradation performance of the graphene composite aerogel. The test results are shown in Table 6.
[0148] Table 6
[0149] Number of cycles <![CDATA[Reaction kinetic rate constant (min -1 )]]> 1 0.25 2 0.23 3 0.24 4 0.22 5 0.23 6 0.24 7 0.22
[0150] It can be seen from Table 6 that the reaction kinetic rate constant of the graphene composite aerogel prepared in Example 3 remains substantially unchanged after being recycled 7 times, and has ideal reusability.
Claims
1. A method for preparing a graphene composite hydrogel, characterized in that: It includes the following steps: The graphene composite hydrogel can be obtained by subjecting a mixed solution of graphene oxide dispersion, noble metal compound, alcohol water-soluble reducing agent and magnetic nanoparticles to irradiation reaction; Among them, in the mixed solution, the mass fraction of the alcohol water-soluble reducing agent is 15%-20%; the alcohol water-soluble reducing agent is methanol, propanol and butanediol; in the mixed solution, the concentration of the magnetic nanoparticles is 0.0050-0.008mmol / ml; the type of the magnetic nanoparticles is ferrosoferric oxide nanoparticles.
2. The method for preparing the graphene composite hydrogel according to claim 1, wherein: The noble metal compound is a water-soluble noble metal compound; And / or, the volume ratio of the methanol, the propanol and the butanediol is (1-3):(1-3):(1-3); And / or, the particle size of the magnetic nanoparticles is 50-500 nm.
3. The method for preparing the graphene composite hydrogel according to claim 1, characterized in that: The particle size of the magnetic nanoparticles is 10-100 nm.
4. The method for preparing the graphene composite hydrogel according to claim 2, characterized in that: The water-soluble precious metal compound is a water-soluble precious metal acid and / or a water-soluble precious metal salt; And / or, the volume ratio of the methanol, the propanol and the butanediol is 1:1:1; And / or, the particle size of the magnetic nanoparticles is 100-200 nm or 200-500 nm.
5. The method for preparing the graphene composite hydrogel according to claim 4, characterized in that: The water-soluble noble metal acid is one or more of chloroauric acid, chloroplatinic acid, chloropalladic acid and chlororhodic acid; And / or, the water-soluble precious metal salt is one or more of silver nitrate, potassium chlororuthenate, potassium chlororhodate, ruthenium trichloride, rhodium trichloride and iridium trichloride.
6. The method for preparing the graphene composite hydrogel according to claim 2, characterized in that: The water-soluble noble metal compound is chloroauric acid, chloroauric acid and chloroplatinic acid, or silver nitrate, potassium chlororuthenate and chloroplatinic acid.
7. The method for preparing the graphene composite hydrogel according to claim 1, characterized in that: The mass ratio of the graphene oxide to the noble metal compound is (1:0.01)-(1:0.4); And / or, the concentration of the graphene oxide is 1-20 mg / mL.
8. The method for preparing the graphene composite hydrogel according to claim 7, characterized in that: The mass ratio of the graphene oxide to the noble metal compound is 1:0.1 or 1:0.2; And / or, the concentration of the graphene oxide is 2-10 mg / mL.
9. The method for preparing the graphene composite hydrogel according to claim 8, characterized in that: The concentration of the graphene oxide is 2 mg / mL.
10. The method for preparing the graphene composite hydrogel according to claim 1, characterized in that: The atmosphere of the irradiation reaction is an oxygen-free atmosphere or an air atmosphere; And / or, the irradiation reaction is performed by irradiation with high-energy rays.
11. The method for preparing the graphene composite hydrogel according to claim 10, characterized in that: The oxygen-free atmosphere is nitrogen and / or argon; And / or, the high-energy rays are gamma rays or electron beam rays; And / or, the dose of the high energy rays is 50-800 kGy; And / or, the dose rate of the high energy rays is 0.1-15 kGy / hour.
12. The method for preparing the graphene composite hydrogel according to claim 11, characterized in that: The gamma ray is cobalt 60 gamma ray; And / or, the dose of the high energy rays is 110-600 kGy; And / or, the dose rate of the high energy rays is 1-15 kGy / hour.
13. The method for preparing the graphene composite hydrogel according to claim 12, characterized in that: The dose of the high-energy rays is 200 kGy; And / or, the dose rate of the high energy rays is 10 kGy / hour.
14. A graphene composite hydrogel prepared by the method for preparing a graphene composite hydrogel as claimed in any one of claims 1 to 13.
15. The graphene composite hydrogel according to claim 14, characterized in that: The pore size distribution of the graphene composite hydrogel is 10-100 μm; and / or, the type of the noble metal nanoparticles in the graphene composite hydrogel is one or more of gold, platinum, palladium, rhodium, silver, ruthenium and iridium; And / or, the diameter of the noble metal nanoparticles in the graphene composite hydrogel is 40-80 nm.
16. A method for preparing a graphene composite aerogel, characterized in that: The method comprises the following steps: drying the graphene composite hydrogel as claimed in claim 14.
17. The method for preparing the graphene composite aerogel according to claim 16, characterized in that: The drying is freeze drying or supercritical carbon dioxide drying.
18. The method for preparing the graphene composite aerogel according to claim 17, characterized in that: The freeze-drying temperature is -40°C.
19. A graphene composite aerogel obtained by the method for preparing a graphene composite aerogel according to any one of claims 16 to 18.
20. The graphene composite aerogel according to claim 19, characterized in that: The pore size distribution of the graphene composite aerogel is 10-100 μm; And / or, the type of the noble metal nanoparticles in the graphene composite aerogel is one or more of gold, platinum, palladium, rhodium, silver, ruthenium and iridium; And / or, the diameter of the noble metal nanoparticles in the graphene composite aerogel is 40-80 nm.
Citation Information
Patent Citations
Graphene aerogel as well as preparation method and application thereof
CN104250005A
Magnetic noble metal catalyst with Raman enhanced activity and preparation method of magnetic noble metal catalyst
CN104549361A
Graphene-noble metal nanoparticle compound hydrogel and aerogel and preparing method and application thereof
CN106268631A